Wanprestasi yang Dilakukan oleh Pihak Debitur Pelaksanaan Perjanjian Kredit Pada Koperasi Dana Rahayu - I B Eka Karanantara; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2020)
To improve the welfare of the community, one of the non-banking institutions is the cooperative providing credit loan facilities for the needs of the community. The aim is as a means of channeling loans or credit for priority communities and people in general. But in reality, the easier the provision of credit services to the public, tends to be a serious problem in the payment of credit. For example, defaults carried out by the community by not implementing the agreed agreement. Therefore the authors are interested in conducting research with the formulation of the problem 1) What are the causes of default by the debtor in the implementation of the loan agreement at Dana Rahayu Cooperative? 2) How do you settle defaults by debtors at the Dana Rahayu Cooperative? The research method used is a empiris research method. The debtor can be said to default if the debtor does not do what he is willing to do, does what he promised is not as promised, does what he promised but is too late, does something that according to the agreement he cannot do. The cause of the default at the Dana Rahayu Cooperative was because the debtor did not pay the arrears for one year and nine months as agreed in the credit agreement. In the Dana Rahayu Cooperative Management Decision, the default made by the debtor on the credit agreement is resolved as far as possible using a family approach to the borrowing member. and it is impossible to do a settlement, the last resort is to carry out the seizure of collateral.